Legal Space for the Creation and Operation of Fintech in Ethiopia - Tewabe, Metages (Bahir Dar University Journal of Law, 2024)
The digital economy is reshaping the global financial system, driving the transformation and development of financial technology irreversibly. Financial technology (Fintech), which combines technology and financial services, has revolutionized how businesses could run. The use of such tools has been steadily increasing in Ethiopia in the last few years and is expected to grow fast. The country’s financial regulator, the National Bank of Ethiopia, is amending a decade-old Payment System law, allowing foreign investors to set up business in this country. The delicate nature of financial systems imperatively requires legal and regulatory systems to regulate Fintech creation and operations. Yet activities related to Fintech are inadequately addressed by the current law in place. The legal or regulatory response is unclear due to the novelty of the products, services, and players. Because of these fragmented and inconsistent regulatory environments, examining Ethiopia’s legal landscape and regulatory frameworks for Fintech has become critical. This article, dedicated to such end, analyze the legal regime for the creation and operation of Fintech under the national bank of Ethiopia regulatory framework. The investigation employed a mixed research methodology with dominant qualitative data generating tools. The evidences from the investigation show that the Ethiopian law in place today does not include technology assessments for Fintech. Additionally, current regulations on Fintech are insufficient because they do not address consumer protection and maintaining consumer trust procedures. Accordingly, the evidences suggest that lawmakers need to create a comprehensive regulatory framework to manage Fintech and pave a way for a healthy development of financial technology.